2006
DOI: 10.1111/j.1600-0749.2006.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers of circulating melanoma cells

Abstract: SummaryOf all skin cancers, cutaneous malignant melanoma (CMM) is the most aggressive and the life expectancy of patients with lymphatic or systemic metastases is dramatically reduced. Understandably therefore, scientists and clinicians have focused on improving diagnostic and prognostic techniques. Of these, perhaps the most promising are multimarker real-time RT-PCR and microarray for detection of circulating CMM cells in peripheral blood. While the optimal set of markers is still to be identified that can a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 94 publications
0
43
1
1
Order By: Relevance
“…Some investigators use target-specific calibrators that allow the accurate quantitation of transcript number within a sample (Trager et al, 2003), although this must be reported relative to transcript number of a housekeeping gene to control for inter-assay variability (especially when different machines and/or thresholds are used). The ability to quantify the level of specific mRNAs also facilitates the development of assays with increased specificity of tumour cell detection where an ideal target has not been identified, overcoming tumour heterogeneity and low-level expression of some target mRNAs in cells of the normal compartments (Cheung and Cheung, 2001;Swerts et al, 2006;Cheung et al, 2007;Medic et al, 2007;Viprey et al, 2008). Where it has not been possible to identify specific wildtype targets for detection of disease, this can be particularly powerful based on the ability to experimentally define a cut-off to distinguish between clinically significant levels of tumour cell mRNA and levels in normal cells (Gunn et al, 1996;Swerts et al, 2006;Cheung et al, 2007).…”
Section: Quantitative (Q)rt-pcrmentioning
confidence: 99%
“…Some investigators use target-specific calibrators that allow the accurate quantitation of transcript number within a sample (Trager et al, 2003), although this must be reported relative to transcript number of a housekeeping gene to control for inter-assay variability (especially when different machines and/or thresholds are used). The ability to quantify the level of specific mRNAs also facilitates the development of assays with increased specificity of tumour cell detection where an ideal target has not been identified, overcoming tumour heterogeneity and low-level expression of some target mRNAs in cells of the normal compartments (Cheung and Cheung, 2001;Swerts et al, 2006;Cheung et al, 2007;Medic et al, 2007;Viprey et al, 2008). Where it has not been possible to identify specific wildtype targets for detection of disease, this can be particularly powerful based on the ability to experimentally define a cut-off to distinguish between clinically significant levels of tumour cell mRNA and levels in normal cells (Gunn et al, 1996;Swerts et al, 2006;Cheung et al, 2007).…”
Section: Quantitative (Q)rt-pcrmentioning
confidence: 99%
“…Indeed, melanoma metastasis reflects to some extent the migratory capacity of melanoblast developmental precursors, the neural crest cells. Moreover, genes that are critical for melanocyte development have been recognised as important factors of melanoma growth, for example MITF, DCT and SOX10 all function to maintain the stem or progenitor cell population of melanoblasts during migration from the neural crest and during melanoblast survival in the hair follicle niche 72,110,[117][118][119] and may be equally important in melanoma cell maintenance and migration. It is important then to identify the expression of these developmental genes in CTCs and assess their association with metastasis.…”
Section: Markers Of Metastasis -Can They Be Identified In Ctcs?mentioning
confidence: 99%
“…From these results it is obvious that; a) CTCs are present at relatively low concentrations; one tumour cell per 10 6 to 10 7 normal blood cells or on average, 1 cell per ml of blood 69,70,71 ; b) the number of cells appears to be related to stage 2,25,72 ; c) melanoma cell markers differ with respect to stage 73 ; and c) CTC gene expression differs from that of the primary tumour 28,29 . Quantitative RT-PCR has typically detected expression of melanocytic genes such as tyrosinase (TYR) 74,75 since normal melanocytes are not thought to circulate in peripheral blood and therefore detection of transcripts from melanocytic genes should correlate to identification of CTCs 72,76 . The sensitivity and specificity of PCR for circulating melanoma cells is increased by analysis of multiple markers 76 , and these commonly include melan-A (MLANA), beta-1,4-N-acetyl-galactosaminyl transferase 1 (B4GALNT1), silver homolog (SILV), melanoma cell adhesion molecule (MCAM), melanoma associated antigen p97 (MFI2), melanoma antigen family A3 (MAGEA3) and microphthalmia-associated transcription factor 4 (MITF4) 63,64,77,78 .…”
Section: Detection Of Ctcsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014 alone, more than 600 publications searchable on PubMed described the diversity of CTP-related isolation techniques, proof-of-principle findings, and implications for human disease management and clinical study design. In melanoma, several reviews have been written to summarize the state of the art in CTP detection, isolation, and genetic characterization, yet its potential contributions to precision medicine remain uncertain [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%